Tactical metrics that discriminate winning, drawing and losing teams in UEFA Euro 2012® - Winter, C.; Pfeiffer, M. (Journal of Sports Sciences, 2016)
The objectives of this article are twofold: first, an innovative approach to notational analysis in football is outlined. By considering the important theoretical requirements for the analysis of sports games (like the interaction between two parties, the procedural sequence of action or the significance of tactical behaviour) the meaning of the introduced parameters, called tactical metrics, is illustrated. In a second step, the validity of this approach is tested using matches of the Union of European Football Associations (UEFA) Euro 2012® to investigate a connection between these metrics and success. The results show that 11 tactical metrics model tactical behaviour in 4 different dimensions (game speed, transition play after ball recovery, transition play after ball loss and offence efficiency (OE)). Discriminant analysis based on the factor values leads to a correct classification of 64.8% identifying winners, losers and drawers. This successful discrimination reveals a connection between match success and the presented metrics. Especially, the transition play after losing the ball and the OE seem to be factors connected directly with the result of a match, since those were important values for a successful discrimination. Furthermore, the procedural description of tactical behaviour provides the opportunity to conduct meaningful recommendations for the training and coaching process.